(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article is based on the research of language corpora conducted by various scholars around the world, who conducted various practical research in various areas of education based on their own research goals and objectives. The article mainly reviewed the practices of foreign countries. Scientists used various corpus-related tools and approaches in their work, you can see these reviewed terms and terms in the list of keywords. The results of the research studies presented in the article are analyzed, and the main results show that experimental groups used the corpus and achieved better results.